PENGARUH EKSTRAK DAUN KETAPANG (Terminalia catappa) TERHADAP HISTOLOGI HATI IKAN NILA (Oreochromis niloticus) YANG DIINFEKSI BAKTERI Aeromonas hydrophila - Khusnul Adinda Arisanti; Efrida Pima Sari Tambunan; Nurlian Augustin Ningrum (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
Aeromonas hydrophila is a rod-shaped bacteria (bacillus), root, motile, with a diameter of 0.3-1 µm and a length of 1-3.5 µm, without a spore phase, generally does not have a capsule and grows optimally at a temperature of 28°C but can grow at extreme temperatures (4°C-37°C). Aeromonas hydrophila causes a disease in fish known as Motile Aeromonas Septicemia (MAS), Aeromonas hydrophila infection can cause liver tissue damage such as fatty degeneration, hemorrhage, necrosis, dilation of the central vein, dilation of hepatocytes, dilation of sinusoids, and changes in the size of the cell nucleus. Ketapang leaves (Terminalia catappa) are known to be rich in active compounds of tannins and flavonoids which have antibacterial properties. This study aims to determine the potential content and efficacy of ketapang leaf extract (Terminalia catappa) in improving the morphology and histology of the liver of tilapia (Oreochromis niloticus) caused by Aeromonas hydrophila bacterial infection. This study used RAL using 30 tilapia (Oreochromis niloticus) which were divided into 6 treatment groups, Normal Control (KN): feed without Aeromonas hydrophila bacterial infection. Negative Control (K-): Aeromonas hydrophila bacterial infection. Positive Control (K+): (fish infected with bacteria + Red Bluedox). Treatment 1: (fish infected with bacteria + 30 ppm ketapang leaf extract). Treatment 2: (fish infected with bacteria + 50 ppm ketapang leaf extract). Treatment 3: (fish infected with bacteria + 70 ppm ketapang leaf extract). The stages in this study included phytochemical screening tests, antioxidant activity tests and morphological and histological examinations of the liver of tilapia (Oreochromis niloticus). Data analysis used one-way ANOVA test and continued with Duncan's advanced test. The results of the study showed that soaking in ketapang leaf extract (Terminalia catappa) had no significant effect on the liver morphology of tilapia fish (Oreochromis niloticus) infected with Aeromonas hydrophila bacteria, while soaking in ketapang leaf extract at a dose of 70 ppm could repair histological damage to the liver of tilapia fish infected with Aeromonas hydrophila, namely with a hemorrhagic damage score (7.75), a fatty degeneration damage score (9.50), and a necrosis damage score (11.00). Meanwhile, histomorphometric observations with a dose of 70 ppm obtained good results for improving the diameter and area of each cell observed, namely the diameter of the central vein (19.54µm), the area of the central vein (306.94µm2), the diameter of hepatocytes (9.03µm), the area of hepatocytes (64.57µm2), the diameter of the hepatocyte nucleus (3.06µm), the area of the hepatocyte nucleus (64.57µm2), the diameter of the sinusoid (7.54µm), and the area of the sinusoid (45.35µm2).